Kurikulum Merdeka for arabic language learning according to Piaget’s cognitive development theory - Ahmad Hidayatullah Zarkasyi; Alin Safaraz Himam; Rahmat Hidayat Lubis; Sintya Kartika Prameswari; Iffatunnisail Badriya (Inovasi Kurikulum, 2023)
The effectiveness of the Arabic educational process can't be separated from the curriculum that has been set and implemented properly. Kurikulum Merdeka, especially in Arabic language learning, is a new curriculum that has not been tested implementatively after its launch and is thought to be not following the level of student learning ability. Jean Piaget has given birth to a comprehensive theory of cognitive development which is the basis for the creation and development of educational curricula in the world. The purpose of cognitive development in Arabic language learning is to increase understanding to obtain new information. This study aims to determine the suitability and analyze the relevance of competence and objectives of Kurikulum Merdeka for Arabic language learning with Jean Piaget's cognitive theory. This study employs a descriptive analysis method along with a qualitative research design. While the method used is the method of observation and literature study. The data used is qualitative in the form of words, sentences, discourse, text, and the entire contents of Kurikulum Merdeka for Arabic language learning. The results of the analysis show that Kurikulum Merdeka for Arabic language learning achieves good results in its suitability and relevance to Jean Piaget's theory of cognitive development. AbstrakKeberhasilan proses belajar mengajar bahasa Arab tidak lepas dari kurikulum yang telah ditetapkan serta diterapkan dengan baik. Kurikulum Merdeka khususnya dalam pembelajaran bahasa Arab merupakan kurikulum baru yang belum teruji secara implementatif setelah diluncurkannya dan diduga belum sesuai dengan tingkatan kemampuan belajar siswa. Jean Piaget telah melahirkan teori perkembangan kognitif yang komprehensif yang menjadi dasar dalam pembuatan dan pengembangan kurikulum pendidikan di dunia. Tujuan perkembangan kognitif dalam pembelajaran bahasa arab adalah untuk meningkatkan pemahaman untuk memperoleh informasi baru. Penelitian ini bertujuan untuk mengetahui kesesuaian dan menganalisis relevansi kompetensi dan tujuan kurikulum Merdeka untuk pembelajaran bahasa Arab dengan teori kognitif Jean Piaget. Desain penelitian ini menggunakan penelitian kualitatif dengan pendekatan deskriptif analisis. Adapun metode penelitian yang digunakan adalah metode observasi dan studi literatur. Data kualitatif yang digunakan berupa kata, kalimat, wacana, teks, dan keseluruhan isi kurikulum Merdeka untuk pembelajaran bahasa Arab. Hasil analisis menunjukkan bahwa Kurikulum Merdeka untuk pembelajaran bahasa Arab mencapai hasil yang baik pada kesesuaian dan relevansinya dengan teori perkembangan kognitif Jean Piaget.Kata Kunci: Kurikulum Merdeka; pembelajaran bahasa Arab; perkembangan kognitif; teori Jean Piaget